The clinical phenotype of systemic sclerosis patients with anti-PM/Scl antibodies: results from the EUSTAR cohort. (12th February 2021) - Lazzaroni, Maria-Grazia; Marasco, Emiliano; Campochiaro, Corrado; DeVries-Bouwstra, Jeska; Gonzalez-Perez, Montserrat-Ixchel; Rojas-Serrano, Jorge; Hachulla, Eric; Zanatta, Elisabetta; Barsotti, Simone; Furini, Federica; Triantafyllias, Konstantinos; Abignano, Giuseppina; et al.
Abstract: Objective: To evaluate clinical associations of anti-PM/Scl antibodies in patients with SSc in a multicentre international cohort, with particular focus on unresolved issues, including scleroderma renal crisis (RC), malignancies, and functional outcome of interstitial lung disease (ILD). Methods: (1) Analysis of SSc patients from the EUSTAR database: 144 anti-PM/Scl+ without SSc-specific autoantibodies were compared with 7202 anti-PM/Scl−, and then to 155 anti-Pm/Scl+ with SSc-specific antibodies. (2) Case–control study: additional data were collected for 165 anti-PM/Scl+ SSc patients (85 from the EUSTAR registry) and compared with 257 anti-PM/Scl− SSc controls, matched for sex, cutaneous subset, disease duration and age at SSc onset. Results: Patients with isolated anti-PM/Scl+, as compared with anti-Pm/Scl−, had higher frequency of muscle involvement, ILD, calcinosis and cutaneous signs of DM, but similar frequency of SRC and malignancies (either synchronous with SSc onset or not). The presence of muscle involvement was associated with a more severe disease phenotype. Although very frequent, ILD had a better functional outcome in cases than in controls. In patients with both anti-PM/Scl and SSc-specific antibodies, a higher frequency of typical SSc features than in those with isolated anti-PM/Scl was observed. Conclusion: The analysis of the largest series of anti-PM/Scl+ SSc patients so far reported helps to delineate a specific clinical subset with muscle involvement, cutaneous DM, calcinosis and ILD characterized by a good functional outcome. SRC and malignancies do not seem to be part of this syndrome.